2014
DOI: 10.1039/c3dt53469c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, antiradical activity and in vitro cytotoxicity of novel organotin complexes based on 2,6-di-tert-butyl-4-mercaptophenol

Abstract: A series of organotin complexes with Sn-S bonds of formulae Me2Sn(SR)2 (1); Et2Sn(SR)2 (2); (n-Bu)2Sn(SR)2 (3); Ph2Sn(SR)2 (4); R2Sn(SR)2 (5); Me3SnSR (6); Ph3SnSR (7) (R = 3,5-di-tert-butyl-4-hydroxyphenyl) were synthesized and characterized by elemental analysis, (1)H, (13)C NMR, and IR. The crystal structures of compounds 1, 4, 5, and 7 were determined by X-ray diffraction analysis. The tetrahedral geometry around the Sn center in the monocrystals of 1, 4, 5, and 7 was confirmed by X-ray crystallography. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(44 citation statements)
references
References 34 publications
1
32
0
6
Order By: Relevance
“…Although it was deduced that tin atoms of TPT react with free sulfhydryl groups in proteins 15 and that TPT induces conformational changes of albumin by hydrophobic forces and forms TPT-albumin complexes 16 , those conclusions were inferred through experiments using active cells but not through direct evidence of interactions between proteins and TPT. Based on functional analysis in the STRING and NCBI databases, most of the proteins interacting with TPT were involved in carbon source, amino acid, fatty acid and energy metabolism; redox processes; and protein synthesis (Supplementary Tables 2–4.…”
Section: Resultsmentioning
confidence: 99%
“…Although it was deduced that tin atoms of TPT react with free sulfhydryl groups in proteins 15 and that TPT induces conformational changes of albumin by hydrophobic forces and forms TPT-albumin complexes 16 , those conclusions were inferred through experiments using active cells but not through direct evidence of interactions between proteins and TPT. Based on functional analysis in the STRING and NCBI databases, most of the proteins interacting with TPT were involved in carbon source, amino acid, fatty acid and energy metabolism; redox processes; and protein synthesis (Supplementary Tables 2–4.…”
Section: Resultsmentioning
confidence: 99%
“…Synthesis of complexes 1–7 from 2,6‐di‐ tert ‐butyl‐4‐mercaptophenol ( L 1 S H) has been reported by us . Starting Schiff base 2‐(N‐3 ′ ,5 ′ ‐di‐ tert ‐butyl‐4 ′ ‐hydroxyphenyl)‐iminomethylphenol ( L 2 ) was prepared as described previously .…”
Section: Methodsmentioning
confidence: 99%
“…The chelating ligands bearing 2,6‐di‐ tert ‐butylphenol pendant were proposed for neutralisation of non‐specific toxicity of organotins . We have recently published the synthesis, antioxidant and cytotoxic properties of organotin thiolates Me 2 Sn(L 1 S) 2 ( 1, L 1 = 3,5‐di‐ tert ‐butyl‐4‐hydroxyphenyl); Et 2 Sn(L 1 S) 2 ( 2 ); Bu 2 Sn(L 1 S) 2 ( 3 ); Ph 2 Sn(L 1 S) 2 ( 4 ); (L 1 ) 2 Sn(L 1 S) 2 ( 5 ); Me 3 Sn(L 1 S) ( 6 ) Ph 3 Sn(L 1 S) ( 7 ) on the base of 2,6‐di‐ tert ‐butyl‐4‐mercaptophenol ( L 1 SH ) . In order to establish possible mechanisms of their cytotoxicity the interaction with tubulin as molecular target and molecular docking were explored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy, the cell apoptosis induction by Sn metal (Shpakovsky et al, 2014); the anti-microbial activity is also known, and has been reported as a pesticide against the flour red scarab or Tribolium casteneum (Win et al, 2012;Kumar and Pankaj, 2014). However, of all the biological activities tried for organotin(IV) compounds, the most noteworthy is the anti-tumoral activity (Sedaghat et al, 2013;Nath et al, 2003 …”
Section: Introductionmentioning
confidence: 99%